Keterampilan Hand Massage Pada Pasien Dan Keluarga Yang Terdiagnosis Diabetes Melitus Tipe 2 Dalam Kontrol Gula Darah Di Desa Darek Wilayah Kerja Puskesmas Darek Kecamatan Praya Barat Daya Kabupaten Lombok Tengah: Emberdayaan Masyarakat Dan Keluarga Dalam Pencegahan Dan Penanganan Awal Ispa Pada Bayi Dan Balita Di Ampenan, Kota Mataram - Marlina Riskawaty, Heny; Istiana, Dian; Arifin, Zaenal (Jurnal LENTERA, 2021)
One of the complication in patients with diabetes mellitus makroangiopati are impaired to streamline. of peripheral blood vessels to the legsThis was due to a decrease in oxygen in the blood that cause failure penghantaran nutrients to tissue in the capillaries occurred because of the increased viscositas hiperglikemik, blood as a result one of the Arterial Periperal Desease ( PAD ) contributing cause ulcers feet in patients. diabetes mellitusThe preventive efforts that can be done is to the care of the feet, in the form of a gymnastic exercise has been shown to increase vaskularisasi. feetIntervention nursing that may be developed by combining the local culture of the hand massage Belian Sasak. research objectives is to improve knowledge about pasie family and hand massage blood sugar control and prevention of foot retinopathy patients diabetes mellitus type 2. The time taken from the preparation up to the one month .Time 1 weeks to preparation and 3 weeks to activities .All patients join the finish this up , and there is increasing the knowledge and lower blood sugar and improve vaskularisasi on foot patients .Is expected in the local community health can partnered with the belian to prevent the increased blood sugar and decline vaskularisasi in patients diabetes mellitus that can cause the foot retinopathy ulcer